Higher education research project: la visión de seis países desarrollados sobre la educación superior necesaria para el nuevo milenio - Salas Madriz, Flora Eugenia (2012)
This article provides a synthesis of the topics and conclusions from the conference Higher Education Reform for Quality Higher Education Management in the 21st. Century. Economical, Technological, Social and Political Forces Affecting Higher Education. This conference took place in Hiroshima, Japan, in 1999. The current situation of higher education in China, Germany, Japan, Singapore, Switzerland and the United States was discussed in this conference which also dealt with issues such as strategic areas, priorities and alternative actions necessary to adjust these university systems to the scientific and technological requirements of the job market in the society of knowledge.